2017
DOI: 10.1007/s10787-017-0324-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute and neuropathic orofacial antinociceptive effect of eucalyptol

Abstract: Terpenes have a wide range of pharmacological properties, including antinociceptive action. The anti-inflammatory and antinociceptive effects of eucalyptol are well established. The purpose of this study was to evaluate the antinociceptive effect of eucalyptol on acute and neuropathic orofacial pain in rodent models. Acute orofacial and corneal nociception was induced with formalin, capsaicin, glutamate and hypertonic saline in mice. In another series, animals were pretreated with capsazepine or ruthenium red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
2
7
0
6
Order By: Relevance
“…Eucalyptol has been shown to exert obvious anti‐inflammatory effects in several inflammatory conditions, including asthma, colitis, cigarette smoke‐induced acute lung inflammation, and influenza virus‐induced infection (Juergens, Stober, Schmidt‐Schilling, Kleuver, & Vetter, ; Kennedy‐Feitosa et al, ; Li et al, ; Santos et al, ). Eucalyptol also possesses analgesic effects in several pain conditions, including neuropathic orofacial pain and pain elicited by application of TRPA1 channel IL‐6, agonists to human skin (Melo Junior et al, ; Takaishi et al, ). Our recent work contributed to these efforts by identifying that eucalyptol produces anti‐inflammatory effects on LPS‐induced pulmonary inflammation and exerts analgesic effects on CFA‐induced mouse model of inflammatory pain as well as acetic acid‐induced visceral pain via interactions with the TRPM8 channel (Caceres et al, ; Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptol has been shown to exert obvious anti‐inflammatory effects in several inflammatory conditions, including asthma, colitis, cigarette smoke‐induced acute lung inflammation, and influenza virus‐induced infection (Juergens, Stober, Schmidt‐Schilling, Kleuver, & Vetter, ; Kennedy‐Feitosa et al, ; Li et al, ; Santos et al, ). Eucalyptol also possesses analgesic effects in several pain conditions, including neuropathic orofacial pain and pain elicited by application of TRPA1 channel IL‐6, agonists to human skin (Melo Junior et al, ; Takaishi et al, ). Our recent work contributed to these efforts by identifying that eucalyptol produces anti‐inflammatory effects on LPS‐induced pulmonary inflammation and exerts analgesic effects on CFA‐induced mouse model of inflammatory pain as well as acetic acid‐induced visceral pain via interactions with the TRPM8 channel (Caceres et al, ; Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptol (1,8-cineole) is the most frequent major constituent of R. officinalis EO, and it has well-established anti-inflammatory and antinociceptive activities [ 185 , 186 ]. Studies have demonstrated that its anti-inflammatory activity occurs by suppression of lipopolysaccharide-induced proinflammatory cytokine production through the action of TNF-α, IL-6, NF-κB, and IL-1β, and reduction of oxidative stress through radical scavenging activity and regulation of signaling pathways [ 187 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…In the joint, the tissues containing nociceptors include primarily the joint capsule, ligaments, synovium, bone, and the outer edge of the menisci (in the knee) [ 10 12 ]. Inflammation lowers the threshold for nociception; while cytokines are being assessed as possible candidates for biochemical markers, inflammation is increasingly being considered as an important part of the pathophysiology of OA [ 13 15 ]. According to the American College of Rheumatology 2000 guidelines, patients with OA of the knee, a condition characterized by cartilage degradation, are often treated with steroids, non-steroidal anti-inflammatory drugs (NSAIDs), and cyclooxygenase-2 selective NSAIDs (e.g., celecoxib), which relieve pain and inflammation but are not capable of restoring tissues once OA has initiated [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%